Sexually differentiated response to choline in choline deficiency and ethionine intoxication. - Tessitore, L. (1995)
A sex difference exists in the response of rats to a choline deficient diet and to ethionine intoxication. Female rats are less susceptible than males to the acute effects of choline deficiency, such as fatty liver and impaired secretion of triglycerides into blood plasma, while they are more susceptible to inhibition of liver protein synthesis and triglyceride accumulation by ethionine. These differences have been ascribed to sex differences in the biosynthesis of phosphatidylcholine in the liver of rats. The available data indicate that females are more dependent than males on the stepwise methylation of phosphatidylethanolamine rather than the direct incorporation of preformed choline. Continuous prefeeding with choline for three weeks was able to shift the female pattern of response to choline deficiency and ethionine intoxication towards that observed in males; thus, choline caused accumulation of hepatic triglycerides and a decrease in plasma triglycerides after choline deficiency, while it protected against ethionine induced triglyceride accumulation and protein synthesis inhibition in the liver. These results suggest that choline prefeeding in females makes them more dependent on choline availability and, thus, more susceptible to a choline deficient diet and less sensitive to ethionine intoxication, as are males. No effect of choline was observed in either choline deficient or ethionine intoxicated male rats.